Math, asked by ranishubhashni, 1 year ago

(a^2-b^2)(a^2+b^2)—(a^2-b^2)^2​

Answers

Answered by aribadesigns73
1

Answer:

Step-by-step explanation:

=(a^2-b^2)(a^2+b^2)-(a^2-b^2)^2

=(a^2-b^2)(a^2+b^2)-(a^2-b^2)(a^2-b^2)  as (a-b)^2=a^2+b^2-2ab=(a-b)(a-b)

=(a^2-b^2)[ (a^2+b^2)-(a^2-b^2)]

=(a^2-b^2)[a^2+b^2-a^2+b^2]     as a^2-a^2=0

=(a^2-b^2)(b^2+b^2)

=(a^2-b^2)(2b^2)

=2a^2.b^2-2b^4 as b^2.b^2=b^2+2=b^4

answer

Answered by BahaWaris
0

Answer:

I can't understand....... .....

Similar questions